Resolution IX International Conference on the Study and Conservation of Birds of Prey of the Working Group on Birds of Prey of Northern Eurasia “Birds of Prey of Northern Eurasia: Research and Conservation”, Dedicated to the Memory of Vladimir Galushin - Igor V. Karyakin; Elvira G. Nikolenko (Пернатые хищники и их охрана)
Resolution IX International Conference on the Study and Conservation of Birds of Prey of the Working Group on Birds of Prey of Northern Eurasia “Birds of Prey of Northern Eurasia: Research and Conservation”, Dedicated to the Memory of Vladimir Galushin, held from September 24 to 27, 2024, on the territory of the Astrakhan Nature Reserve (Russia).